Her unfearing mind : women and Muslim laws in Bangladesh - Kamal, Sultana; Āina Sāliśa Kendra (Dhaka, Bangladesh); Research Project on Women and Law in the Muslim World; Women Living Under Muslim Laws (Organization) (Dhaka : Ain o Salish Kendro, 2001)
Report of the Research Project on Women and Law in the Muslim World conducted by the international solidarity network of Women Living Under Muslim Laws.
Includes bibliographical references (p. [154]).
Keywords: Women -- Legal status, laws, etc. -- Bangladesh; Women (Islamic law) -- Bangladesh